Memperkenalkan Sejarah melalui Pendekatan Komunikasi Visual: Studi Kasus Cerita Ken Arok dan Ken Dedes: Introducing History through a Visual Communication Approach: Case Study of Ken Arok and Ken Dedes Story - Prianti, Desi Dwi; Amilia, Mona Fauziah; Handayani, Sri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The development of communication technology has often not aligned with efforts to foster children’s interest in history. History, which often focuses on narratives of past suffering or becomes entangled in debates over truth, tends to be perceived as uninspiring and unappealing. As a result, history is increasingly overlooked, particularly by children, amid the dominance of pop culture. Through a visual communication approach, this community service program developed child-friendly historical narratives and actively involved children as participants. The story of Ken Arok and Ken Dedes, rooted in the history of the Singosari Kingdom in Malang, was chosen as the learning material due to its significance as an important part of local history. The program engaged students of TK Dharma Putra Malang as the participants. This program uses audio-visual design products, storytelling activities based on story books, using activity books as tools of historical learning for kindergarten students, while the students are accompanied by the facilitators who consist of the members of the Community Service team and also the teachers of the school. This approach not only aimed to introduce history to children but also sought to cultivate their interest and pride in the legacy of local culture. The community service initiative demonstrates that introducing history through creative media can enhance children’s enthusiasm and participation in learning history. This program is intended to inspire enjoyable and effective ways of teaching history in the digital age.